1997
DOI: 10.1177/014107689709000404
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Endocrinopathy: A Legacy of Insults

Abstract: Over the past 35 years, oncologists have vastly improved the survival figures for several malignant diseases, especially the common varieties seen in childhood. What is the quality of life in the many survivors? One aspect that has generated much attention is endocrine function.Radiation can directly impair hypothalamic, pituitary, thyroid, pancreatic and gonadal function as well as predisposing to development of hyperparathyroidism, and thyroid adenomas or carcinomas. Cytotoxic chemotherapy can damage the gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Previous reports demonstrated that hypothalamic damage induced by radiation therapy, traumatic brain injury, or subarachnoid hemorrhage could cause deficiency of one or more anterior pituitary hormones. 27-30 Interestingly, most of these reports demonstrated that growth hormone was the most vulnerable, but this study showed that thyroid and corticosterone deficiencies were frequent. Although the difference in mechanisms was unclear, protection of at least one side of the hypothalamus is believed to be important for preserving hypothalamic regulation of pituitary function.…”
Section: Discussionmentioning
confidence: 60%
“…Previous reports demonstrated that hypothalamic damage induced by radiation therapy, traumatic brain injury, or subarachnoid hemorrhage could cause deficiency of one or more anterior pituitary hormones. 27-30 Interestingly, most of these reports demonstrated that growth hormone was the most vulnerable, but this study showed that thyroid and corticosterone deficiencies were frequent. Although the difference in mechanisms was unclear, protection of at least one side of the hypothalamus is believed to be important for preserving hypothalamic regulation of pituitary function.…”
Section: Discussionmentioning
confidence: 60%
“…167 Chemotherapy treatment can induce azoospermia, which is permanent in most cases. 168 [Evidence level 3]…”
Section: Prescribed Drug Usementioning
confidence: 99%
“…103 Chemotherapy treamnet may lead to azoospermia, which, in most cases, is permanent. 104 Among recreational drugs, anabolic steroids and cocaine can have adverse effect on the semen quality. [105][106][107] Genetic and chromosomal alteration, after all, has its role to play in human azoospermia.…”
mentioning
confidence: 99%